Turbulent transport driven by kinetic ballooning modes in the inner core of JET hybrid H-modes. (22nd January 2021) - Kumar, N.; Camenen, Y.; Benkadda, S.; Bourdelle, C.; Loarte, A.; Polevoi, A.R.; Widmer, F.; contributors, JET
Abstract: Turbulent transport in the inner core of the high- β JET hybrid discharge 75225 is investigated extensively through linear and non-linear gyro-kinetic (GK) simulations using the GK code GKW in the local approximation limit. Compared to previous studies (Citrin et al 2015 Plasma Phys. Control. Fusion 57 014032; Garcia et al 2015 Nucl. Fusion 55 053007), the analysis has been extended towards the magnetic axis, ρ < 0.3, where the turbulence characteristics remain an open question. Understanding turbulent transport in this region is crucial to predict core profile peaking that in turn will impact the fusion reactions and the tungsten neoclassical transport, in present devices as well as in ITER. At ρ = 0.15, a linear stability analysis indicates that kinetic ballooning modes (KBMs) dominate, with an extended mode structure in ballooning space due to the low magnetic shear. The sensitivity of KBM stability to main plasma parameters is investigated. In the non-linear regime, the turbulence induced by these KBMs drives a significant ion and electron heat flux. Standard quasi-linear (QL) models are compared to the non-linear results. The standard reduced QL models work well for the E × B fluxes, but fail to capture magnetic flutter contribution to the electron heat flux induced by the non-linear excitation of low k θ ρ i micro-tearing modes that are linearly stable. An extension of the QL models is proposed allowing better capturing the magnetic flutter flux.